Analisis Kemampuan Efektif Membaca (KEM) Mahasiswa Program Studi Pendidikan Guru Madrasah Ibtidaiyah UIN Mahmud Yunus Batusangkar - Ratmiati, Ratmiati; Setiawan, Eko Muda (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2025)
Reading ability is still a challenge for students both in terms of speed and comprehension. Students only read readings without paying attention to reading comprehension and speed. This study aims to determine the level of students' reading speed and comprehension. The data is then analyzed and described in the form of statistical data using quantitative research methods. The research sample was students of the PGMI Study Program, UIN Mahmud Yunus Batusangkar, Class of 2022 (semester 5) from four classes (A-D) with a total sample of 132 students. The technique used in this study was the Test Technique. In the process, the researcher distributed test materials in the form of scientific readings totaling 325 words and a test in the form of short answer questions totaling 10 questions to test students' understanding of the contents of the reading. Quantitative data analysis techniques were used to analyze the results of the reading comprehension test in the form of average values of Reading Speed (KM), Content Comprehension (PI), and Effective Reading Ability (KEM). The results showed that students' KM was 213.76 wpm, this shows that students' reading speed is still below the standard that must be obtained at the student level, namely 325 wpm. PI is 55.68% which indicates the less category. While KEM is 117.95% which is in the very low category. The factors that influence students' reading ability are (1) lack of knowledge about the correct reading techniques, (2) lack of students' interest in reading, and (3) lack of direction and guidance from teachers or lecturers about reading.